Electromagnetic fields - Bladel, Jean G. Van (IEEE (Institute of Electrical and Electronics Engineers), 2007)
Electromagnetic Fields, Second Edition includes: Detailed discussions of electrostatic fields, potential theory, propagation in waveguides and unbounded space, scattering by obstacles, penetration through apertures, and field behavior at high and low frequencies; Many analytical developments suitable for exploitation by the numerical analyst, including the popular method of moments; Comprehensive discussion of singularities of sources and fields with delineations of field properties at edges and at sector and cone vertices; Extensive appendices that of themselves are worth the cost of the book ; A large, useful, carefully compiled set of references; Extensive appendices that of themselves are worth the cost of the book ; A large, useful, carefully compiled set of references